Effect of vermicompost leachate on lettuce germination in vitro (Nexo Revista Científica, 2024)
Given the pressing global population growth and the escalating demand for food, the adoption of sustainable agricultural practices has become a necessity. In this context, the use of vermicompost leachate (VCL), a nutrient and microorganism-rich organic alternative to chemical fertilizers, has gained significant attention. However, its application necessitates careful consideration due to the potential phytotoxicity it may pose. The experiment was designed to evaluate the effects of various VCL concentrations on lettuce seed germination, vegetative development, photosynthetic pigments, and phytotoxicity in vitro. The concentrations tested ranged from 2.0% to 4.0%. The results revealed a concentration-dependent effect, with lower concentrations (2.0%-2.5%) showing neutral or positive effects on germination and growth, and higher concentrations (3.5%-4.0%) demonstrating phytotoxic effects, leading to reduced germination rates and impaired seedling growth. The analysis of photosynthetic pigments further supported these findings, showing a decrease with increasing VCL concentrations. Principal component analysis further highlighted the concentration-dependent effects of VCL on seed germination and growth. While lower concentrations correlated positively with germination and growth parameters, higher concentrations exhibited negative correlations, indicating greater phytotoxicity. These findings highlighted the complex interplay between VCL concentrations and their effects on seedling growth and development.